Interaction in motion: designing truly mobile interaction - Marshall, Joe; Dancu, Alexandru; Mueller, Florian ‘Floyd' (2016)
The use of technology while being mobile now takes place in many areas of people’s lives in a wide range of scenarios, for example users cycle, climb, run and even swim while interacting with devices. Conflict between locomotion and system use can reduce interaction performance and also the ability to safely move. We discuss the risks of such “interaction in motion”, which we argue make it desirable to design with locomotion in mind. To aid such design we present a taxonomy and framework based on two key dimensions: relation of interaction task to locomotion task, and the amount that a locomotion activity inhibits use of input and output interfaces. We accompany this with four strategies for interaction in motion. With this work, we ultimately aim to enhance our understanding of what being “mobile” actually means for interaction, and help practitioners design truly mobile interactions.